STRATEGI PENGEMBANGAN KURIKULUM DAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Siti Halimah (State Islamic University North Sumatra, 2009)
Abstract: The Strategy of Curriculum Developt and Islamic Religious Education Learning. Islamic education is frequently criticized for not producing the desired attitudes and behaviors. Many factors have been suggested as being behind this problem, the most important being related to curriculum and methodology. In addition to design problems, Islamic education curriculum is too cognitive in nature and unable to adapt to changes. The prevalent methodology is not effective in processing cognitive knowledge into well internalized values that guide attitudes and behaviors. Our present author strongly suggests that any program to develop Islamic education must start with or at least take curriculum and methodologyinto serious consideration.Kata Kunci: kurikulum, pembelajaran